The Characterization of Wave Parameters in Laboratory Scale of Wave Simulator Using Video Tracking Analysis - Syafitri, Nur Linda; Ekawati, Riska; Yuliza, Elfi (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2023)
Understanding the wave parameters in the ocean wave phenomenon is necessary to learn and develop the potential of ocean wave energy. Therefore, this study created a simple laboratory-scale of wave simulator that was developed using an electric motor. The various wave parameters obtained by different treatments were carried out using variations in the angle of the wedge inclination and the rotational speed of the wave generator. In this system, two pulleys of different sizes were used, a large pulley with a diameter of 20 cm and a small pulley with a diameter varying between 1.25 cm and 1.98 cm. Changing the size of the pulleys uses the principle of axial rotational motion to produce different rotational speeds. Moreover, the video tracker analysis application was used to characterize the parameters of the waves generated in the simulator that has been designed. The parameters obtained include wave height, amplitude, frequency, wave period, wavelength, and wave propagation speed. In the examination and analysis that have been carried out, it has been found that increasing wave height and amplitude correlates with increasing the inclination of wedges. The frequency and speed of the waves are linearly related to changes in the rotation speed of the wave generator. For the characteristic wavelength, there is inverse relation to the rotational speed. Based on this study, the wave simulator system and video tracking analysis application can be used to increase the understanding of wave parameters. In addition, this research can also be used as preliminary research on developing a prototype for an ocean wave energy converter on the laboratory scale.